Arabidopsis RSS1 Mediates Cross-Talk Between Glucose and Light Signaling During Hypocotyl Elongation Growth. Issue 1 (December 2017) - Singh, Manjul; Gupta, Aditi; Singh, Dhriti; Khurana, Jitendra; Laxmi, Ashverya
Abstract Plants possess exuberant plasticity that facilitates its ability to adapt and survive under challenging environmental conditions. The developmental plasticity largely depends upon cellular elongation which is governed by a complex network of environmental and phytohormonal signals. Here, we report role of glucose (Glc) and Glc-regulated factors in controlling elongation growth and shade response in Arabidopsis. Glc controls shade induced hypocotyl elongation in a dose dependent manner. We have identified a Glc repressed factorREGULATED BY SUGAR AND SHADE1 (RSS1 ) encoding for an atypical basic helix-loop-helix (bHLH) protein of unknown biological function that is required for normal Glc actions. Phenotype analysis of mutant and overexpression lines suggested RSS1 to be a negative regulator of elongation growth. RSS1 affects overall auxin homeostasis. RSS1 interacts with the elongation growth-promoting proteins HOMOLOG OF BEE2 INTERACTING WITH IBH 1 (HBI1) and BR ENHANCED EXPRESSION2 (BEE2) and negatively affects the transcription of their downstream targets such asYUCs, INDOLE-3-ACETIC ACID INDUCIBLE (IAAs ), LONG HYPOCOTYL IN FAR-RED1 (HFR1 ), HOMEOBOX PROTEIN 2 (ATHB2 ), XYLOGLUCAN ENDOTRANSGLUCOSYLASE/HYDROLASES (XTHs ) andEXPANSINS . We propose, Glc signals might maintain optimal hypocotyl elongation under multiple signals such as light, shade and phytohormones through the central growth regulatory bHLH/HLH module.